Sugammadex and Reversal of Neuromuscular Block in Adult Patient with Duchenne Muscular Dystrophy - Ahmed Abdelgawwad Wefki Abdelgawwad Shousha; Maria Sanfilippo; Antonio Sabba; Paolo Pinchera (Case Reports in Anesthesiology)
Duchenne’s muscular dystrophy (DMD) is the most common and severe form of myopathy. Patients with DMD are more sensitive to sedative, anesthetic, and neuromuscular blocking agents which may result in intraoperative and early postoperative cardiovascular and respiratory complications, as well as prolonged recovery from anesthesia. In this case report, we describe a 25-year-old male patient admitted for cholecystectomy under general anesthesia. We induced our anesthesia by oxygen, propofol, fentanyl, and rocuronium bromide. Maintenance was done by fentanyl, rocuronium bromide, sevoflurane, and O2. We report in this case the safety use of sugammadex to antagonize the neuromuscular block and rapid recovery in such category of patients.